2008
DOI: 10.1152/ajpcell.00542.2007
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the signaling network of COX-2 induction in sheared chondrocytes: COX-2 is induced via a Rac/MEKK1/MKK7/JNK2/c-Jun-C/EBPβ-dependent pathway

Abstract: Shear stress is a pathophysiologically relevant mechanical signal in cartilage biology and tissue engineering. Cyclooxygenase-2 (COX-2) is a pivotal proinflammatory enzyme, which is induced by mechanical loading-derived shear stress in chondrocytes. In the present study, we investigated the transcriptional machinery and signaling pathway regulating shear-induced COX-2 expression in human chondrocytic cells. Deletion and mutation analyses of the human cox-2 promoter reveal that the CCAAT/enhancer-binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 58 publications
7
36
0
Order By: Relevance
“…Through the use of RNAi, we demonstrated the functional role of the NF-B p65 subunit in shear-induced IL-6 mRNA synthesis in human T/C-28a2 chondrocytes. In agreement with our previously published results (17), p65 knockdown did not affect the extent of shearinduced COX-2 expression in chondrocytes (data not shown), thereby suggesting that COX-2 is upstream of NF-B and eliminating the possibility of a feedback mechanism from NF-B to COX-2. The key role of NF-B in shear-induced IL-6 transcriptional activity is further demonstrated by the use of wild-type and NF-B mutated IL-6 promoterreporter constructs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Through the use of RNAi, we demonstrated the functional role of the NF-B p65 subunit in shear-induced IL-6 mRNA synthesis in human T/C-28a2 chondrocytes. In agreement with our previously published results (17), p65 knockdown did not affect the extent of shearinduced COX-2 expression in chondrocytes (data not shown), thereby suggesting that COX-2 is upstream of NF-B and eliminating the possibility of a feedback mechanism from NF-B to COX-2. The key role of NF-B in shear-induced IL-6 transcriptional activity is further demonstrated by the use of wild-type and NF-B mutated IL-6 promoterreporter constructs.…”
Section: Discussionsupporting
confidence: 93%
“…In view of previous observations showing a positive correlation between endogenous COX-2-mediated PGE 2 production and IL-6 synthesis (24, 25), we first evaluated the effects of shear stress on COX-2 expression and formation of cAMP, because PGE 2 is a well-known activator of the cAMP signaling pathway. In accord with prior data (17), high shear stress (20 dyn/cm 2 ) rapidly induces COX-2 mRNA (Fig. 1A) and protein (Fig.…”
Section: Shear Stress Induces Il-6 Expression In Human Chondrocytes Vsupporting
confidence: 92%
See 2 more Smart Citations
“…It seemed that there was a threshold level between 3.1 and 7.5 dyne/ cm 2 . Previous study also found that COX-2 expression could be detected above the threshold level of 5 dyne/cm 2 in chondrocytes, which correlated well with our current results (Healy et al 2008). Therefore, our finding suggested that moderate level of stimulation could also result in detrimental cytokine release in chondrocytes.…”
Section: Discussionsupporting
confidence: 93%